Co-delivery of p53 and MDM2 inhibitor RG7388 using a hydroxyl terminal PAMAM dendrimer derivative for synergistic cancer therapy. (December 2019) - Chen, Kang; Xin, Xiu; Qiu, Lipeng; Li, Wenpan; Guan, Guannan; Li, Gang; Qiao, Mingxi; Zhao, Xiuli; Hu, Haiyang; Chen, Dawei
Abstract: P53 inactivation is often achieved through gene mutation and the excessive activity of its major negative regulator, murine double minute 2 protein (MDM2). In the present study we utilized a PAMAM-OH derivative (PAMSPF) to co-deliver p53 plasmid and MDM2 inhibitor (RG7388) to the tumor site and evaluated the synergistic anti-tumor effect of p53 plasmid and RG7388. PAMSPF was able to condense DNA and encapsulate RG7388 to form spherical nanoparticles (PAMSPF/p53/RG) with particle sizes of around 200 nm, and remain stable in the presence of heparin and nuclease. The drug loading capacity and encapsulation efficiency of RG7388 in PAMSPF/p53/RG were 0.5% and 92.5%, respectively. The p53 expressions in MDA-MB-435, p53-wild type MCF-7 cells (MCF-7/WT) and p53-silenced MCF-7 cells (MCF-7/S) treated with PAMSPF/p53/RG were promoted significantly. As a result, PAMSPF/p53/RG was able to inhibit cell proliferation, arrest cell cycle, and induce cell apoptosis of MDA-MB-435, MCF-7/WT and MCF-7/S cells. PAMSPF/p53/RG suppressed human umbilical vascular endothelial cells (HUVECs) migration, invasion and tube formation through decreasing the VEGF expression. And the biological activities described above of PAMSPF/p53/RG were significantly higher than those of PAMSPF/53 and PAMSPF/RG, exhibiting the synergistic actions of p53 plasmid and RG7388. In addition, intravenous administration of PAMPSF/p53/RG inhibited tumor growth of MDA-MB-435 and MCF-7/WT xenograft mice models, and induced no substantial weight loss. PAMSPF/p53/RG also reduced cell proliferation, and induced cell apoptosis in vivo based on the immunohistochemistry results. Collectively, PAMSPF/p53/RG is an excellent system for gene and drug co-delivery, and the combined treatment of p53 plasmid and RG7388 possesses a synergistic antitumor activity both in vitro and in vivo . Statement of significance: In the present study we utilized a PAMAM-OH derivative (PAMSPF) to co-deliver p53 plasmid and RG7388 (MDM2 inhibitor) and evaluated their synergistic anti-tumor effect. PAMSPF could condense p53 plasmid and encapsulate RG7388 to form nanoparticles (PAMSPF/p53/RG). The p53 expressions in MDA-MB-435, p53-wild type MCF-7 cells (MCF-7/WT) and p53-silenced MCF-7 cells (MCF-7/S) treated with PAMSPF/p53/RG were promoted significantly. As a result, PAMSPF/p53/RG could inhibit cell proliferation, arrest cell cycle, and induce cell apoptosis of three kinds of cells. In addition, intravenous administration of PAMPSF/p53/RG inhibited tumor growth of MDA-MB-435 and MCF-7/WT xenograft mice models. Collectively, PAMSPF/p53/RG is an excellent system for gene and drug co-delivery, and the combined treatment of p53 plasmid and RG7388 possesses a synergistic antitumor activity. Graphical abstract: Image, graphical abstract